Determinants of long‐term care service use by persons with dementia: A national dementia registry study conducted in Taiwan. (18th April 2022) - Tsai, Chia‐Fen; Huang, Mao‐Hsuan; Cheng, Chih‐Ming; Lee, Jun‐Jun; Wang, Wen‐Fu; Huang, Ling‐Chun; Huang, Li‐Kai; Lee, Wei‐Ju; Sung, Pi‐Shan; Liu, Yi‐Chien; Ouyang, Wen‐Chen; Hsu, Chih‐Cheng; et al.
Abstract: Background: This study investigated the determinants and use of Taiwan's long‐term care (LTC) Plan Version 2.0 (LTC 2.0) services by persons with dementia (PWDs) and their caregivers. Methods: In total, 1268 PWD–caregiver dyads were enrolled for analysis from a national dementia registry. Andersen's Behavioral Model of Health Services Use was used to investigate the association of LTC service use with several factors, namely the demographic data of PWDs and their caregivers, migrant caregiver employment, monthly household income, caregiver burden as determined by the Zarit Burden Interview (ZBI), Mini‐Mental State Examination score, Clinical Dementia Rating scores, neuropsychiatric inventory scores for the behavioral and psychological symptoms of dementia, and PWDs' activities of daily living (ADLs). Results: Among the studied family caregivers, 81.4% did not use LTC resources. A multivariable logistic analysis revealed that aberrant motor behaviors (odd ratio [OR] = 1.31, 95% confidence interval [CI] = 1.10–1.56, p  = 0.003), dysfunction in ADLs (OR = 1.06, 95% CI = 1.02–1.10, p  = 0.002), higher ZBI scores (OR = 1.02, 95% CI = 1.01–1.03, p  = 0.004), not residing with family members (OR = 1.88, 95% CI = 1.32–2.66, p  < 0.001), and not employing a migrant caregiver (OR = 4.41, 95% CI = 2.59–7.51, p  < 0.001) were the factors most significantly associated with LTC service use. Conclusion: Factors such as whether PWDs live alone, specific neuropsychiatric symptoms, and impaired function should be considered in future policy amendments to provide required activities and care resources for PWDs and their caregivers. Key points: This study investigated the determinants and use of long‐term care (LTC) service by persons with dementia (PWDs) and their caregivers. PWDs who used LTC services had more severe neuropsychiatric symptoms (NPSs), poorer cognitive function, and inferior ability to engage in activities of daily living (ADLs) and placed a greater burden on their caregivers. More aberrant motor behaviors, greater ADL limitations, greater caregiver burden, not residing with family members, and not employing migrant caregivers were the factors most significantly associated with LTC service use. These factors should be considered in future policy amendments to provide care resources for PWDs and meet the needs of PWDs and their caregivers.